Investigating the Effect of Thinking Styles on Forgiveness with the Mediating Role of Executive Functions in Recovered and Unrecovered Adolescents with Self-Injury - Majdi, Maral; Jahanpeyma, Nazanin; Razi, Maryam; Omidi, Azam; Erfani, Nilofrasadat (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to explore how different thinking styles affect self-forgiveness in adolescents who self-injure, taking into account the role of executive functions in recovery compared to non-recovery.Methodology: A descriptive-correlational approach was used for this cross-sectional study, employing structural modeling and multi-group analysis (MGA). The study included all adolescents in Tehran with a history of self-harm between September and November 2023, with a sample of 111 adolescents selected through purposive sampling. Instruments utilized were the Thinking Styles Inventory (TSI), Executive Functions Questionnaire (EFQ), and Enright Forgiveness Inventory–30 (EFI-30). Statistical analysis was conducted using SPSS version 27 for descriptive statistics and Independent Samples T-Test, as well as SmartPLS version 4 for path analysis and Multi-group Analysis (MGA), with a significance level set at 0.05.Findings: The study found that Inhibition, Organizing, and Planning decision-making functions did not significantly impact self-forgiveness in the Recovered Adolescents group, while the Planning decision-making function had a positive and significant influence on self-forgiveness in the Unrecovered Adolescents group (p = 0.043). Similarly, the Type 1 Thinking Style had a positive and significant effect on self-forgiveness in the Recovered Adolescents group (B = 0.872, p = 0.000).Conclusion: The results indicated that recovered adolescents exhibited a Type 1 thinking style and higher executive functions, correlating with greater levels of self-forgiveness. Conversely, non-recovered adolescents tended to have a Type II thinking style, with only the planning function contributing to increased self-forgiveness in this group. These findings highlight the significance of cognitive and psychological factors in the recovery process from self-injury.